2018
DOI: 10.1111/asj.13154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isonitrogenous and isocaloric total mixed ration composed of forages with different quality on milk fatty acid composition and gene expression of mammary lipogenic enzymes in mid‐lactating dairy cows

Abstract: The aim of this study was to determine the effects of isonitrogenous and isocaloric diets containing different qualities of forages and concentrate content on milk fat composition and genes that encode mammary lipogenic enzymes in dairy cows. A total of 20 Holstein cows were assigned to 1 of 2 treatment diets composed of either mixed forages (MF, starch : 21.50%) or corn stover forage (CS, starch : 25.39%). Mammary tissue biopsies were performed to analyze the mRNA expression of lipogenic enzymes. Dry matter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Interestingly, in adipose tissue prolactin appears to inhibit LPL activity during lactation, at the least in humans [187], to augment availability of FA to the mammary tissue [188]. Transcription of LPL in bovine mammary is also affected by diet as observed in dairy goats and cows [189][190][191].…”
Section: Hydrolysis Of Tag In Lipoproteins By Lipasesmentioning
confidence: 99%
“…Interestingly, in adipose tissue prolactin appears to inhibit LPL activity during lactation, at the least in humans [187], to augment availability of FA to the mammary tissue [188]. Transcription of LPL in bovine mammary is also affected by diet as observed in dairy goats and cows [189][190][191].…”
Section: Hydrolysis Of Tag In Lipoproteins By Lipasesmentioning
confidence: 99%
“…Among these factors, the diet, whether or not mediated by the rumen metabolism, has a pivotal role since it can deeply modify the organoleptic and nutraceutical quality of both milk and dairy products. Several studies have demonstrated that pasture-based diets can positively influence milk nutrient profile improving the concentration of several beneficial compounds such as Omega-3 polyunsaturated fatty acids, vaccenic and linolenic acid, and conjugated linoleic acid (CLA), as well as reducing the levels of Omega-6 fatty acids and palmitic acid [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%